Leakage and comparative advantage implications of agricultural participation in greenhouse gas emission mitigation - Heng-Chi Lee; Bruce A. McCarl; Uwe A. Schneider; Chi-Chung Chen (The University of Western Ontario, Department of Economics, 2004)
The world is moving toward efforts to reduce greenhouse gas emissions. Net emission reduction efforts may involve the agricultural sector through options such as planting of trees, crop and livestock management changes, and production of biofuels. However, such options can be competitive with domestic food production. In a free trade arena, reduced domestic food production could stimulate increased production and exports in other countries, which are not pursuing similar mitigative courses of action. As a consequence, net emission reductions in implementing countries may be offset by activities stimulated in other countries. In addition producers in countries where agriculture is subject to greenhouse gas mitigation have expressed concern about their competitive position to countries which are not trying to reduce net emissions. We examine the competitive effects of differential mitigation efforts on agricultural food production and on international trade. In doing this we employ the assumption that the average U.S. compliance caused cost increase would also occur in other complying countries. We consider implementation: 1) unilaterally by the U.S., 2) by all Kyoto Protocol Annex I countries and 3) globally. The results, which are only suggestive of the types of effects that would be observed due to the simplifying cost assumptions, indicate compliance causes supply cutbacks in regulated countries and increases in non-regulated countries. In addition, the study results show that U.S. agricultural producers are more likely to benefit from a Kyoto Protocol like environment but that consumers are likely to be hurt in terms of their agricultural welfare.
Keywords: Q54; Q58; 330; leakage; international trade; agricultural and forest sector; greenhouse gas; mitigation implementation